The Mycobacterium bovis BCG prime-Rv0577 DNA boost vaccination induces a durable Th1 immune response in mice - Gu, Dongqing (Acta Biochim Biophys Sin (Shanghai), 2016)
Tuberculosis remains a major global health problem and effective vaccines are urgently needed. In this study, we used the combined DNA- and protein-based vaccines of immunodominant antigen Rv0577 to boost BCG and evaluated their immunogenicity in BALB/c mice. Our data suggest that the booster vaccine may substantially enhance the immunogenicity of BCG and strengthen both CD4+ T cell-mediated Th1 and CD8+ T cell-mediated cytolytic responses. Compared with the protein-based vaccine, the DNA-based vaccine can induce more durable Th1 immune response, characterized by high levels of antibody response, proliferation response, percentages of CD4+/CD8+ and cytokine secretion in antigen-stimulated splenocyte cultures. In conclusion, we for the first time, developed a protein- and plasmid DNA-based booster vaccine based on Rv0577. Our findings suggest that antigen Rv0577-based DNA vaccine is immunogenic and can efficiently boost BCG, which could be helpful in the design of an efficient vaccination strategy against TB.